2014
DOI: 10.1186/1471-2458-14-876
|View full text |Cite
|
Sign up to set email alerts
|

‘I heard about this study on the radio’: using community radio to strengthen Good Participatory Practice in HIV prevention trials

Abstract: BackgroundDuring the Microbicides Development Program (MDP) 301, a clinical trial of a candidate microbicide amongst women in Johannesburg, South Africa, we used community radio to promote awareness of the trial, to inform community members about specific medical research procedures and terminologies, and to stimulate dialogue between researchers and local citizens.MethodsWe used mixed methods to undertake a retrospective analysis of the social responses to the radio shows, focusing specifically on recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In 2013, Sierra Leone had a literacy rate of only 46% ( 25 ), which makes radio the preferred and most accessible source of information for a large part of the population (78% have access to radio) ( 26 ). Other studies have also reported the importance of radio in promoting knowledge in low-income settings ( 11 , 27 , 28 ). Nonetheless, the influence of radio on promoting protective behavior in these studies was not as strong ( 11 ) or did not have an association at all ( 28 ).…”
Section: Discussionmentioning
confidence: 92%
“…In 2013, Sierra Leone had a literacy rate of only 46% ( 25 ), which makes radio the preferred and most accessible source of information for a large part of the population (78% have access to radio) ( 26 ). Other studies have also reported the importance of radio in promoting knowledge in low-income settings ( 11 , 27 , 28 ). Nonetheless, the influence of radio on promoting protective behavior in these studies was not as strong ( 11 ) or did not have an association at all ( 28 ).…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, fewer studies conducted stakeholder engagement in middle‐ (30 studies; 27.8%) 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100 and low‐income (nine studies; 8.3%) 101, 102, 103, 104, 105, 106, 107, 108, 109 countries. The location of stakeholder engagement could not be discerned in six studies (5.6%) 110, 111, 112, 113, 114, 115, and fifteen studies (13.9%) 16, 24, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128 conducted stakeholder engagement in multiple countries at different income levels.…”
Section: Resultsmentioning
confidence: 99%
“…• raise awareness about health-related issues (Hlongwana, Zitha, Mabuza & Maharaj, 2011;Mawokomayi & Osunkunle, 2019;Medeossi, Stadler & Delany-Moretlwe, 2014). • inform and empower women (Fombad & Jiyane, 2019;Oduaran & Nelson, 2019).…”
Section: Assessing the Social Media Maturity Of A Community Radio Stamentioning
confidence: 99%